Atypical Mandibular Osteomyelitis in an Ewe Caused by Coinfection of Pseudomonas aeruginosa and Lactococcus raffinolactis - Garcia Motta, Rodrigo; Martinez, Antonio Campanha; Pereira Junior, Oduvaldo Câmara Marques; Martins, Lorrayne de Souza Araújo; Paz, Jéssica Priscila da; Bello, Thaís Spessotto; Árabe Filho, Marcelo Fagali; Ribeiro, Marcio Garcia (Acta Scientiae Veterinariae, 2022)
Background: Osteomyelitis is defined as a bone inflammation involving the cortical and medullary regions, usually caused by the local invasion of opportunistic microorganisms. The inflammatory reaction of bone may extend to the periosteum and soft tissues, compromising adjacent structures far from the initially infected foci. Different classifications of transmission routes, gravity levels, and tissues involved in animal and human osteomyelitis are available. In humans, the infection can reach bone tissue by exogenous or hematogenous pathways. This paper reports an atypical case of mandibular pyogranulomatous osteomyelitis in an ewe caused by concomitant Pseudomonas aeruginosa and Lactococcus raffinolactis infection. Case: The animal presented a 1-month history of progressive mandibular enlargement refractory to conventional therapy. In a physical examination, an increased volume located in the ventrolateral region of the right ramus of the mandible was observed. Fine-needle aspiration of the lesion enabled isolation in bacteriological culture of Pseudomonas aeruginosa and Lactococcus raffinolactis using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Besides support care procedures and antimicrobial treatment approaches for the sheep based on in vitro tests, the animal died due to the severity of the clinical signs and the progressive worsening of the general health status. The radiographic image examination of the mandibular region revealed a severe and infiltrative periodontal reaction, with a predominance of a great number of neutrophils and macrophages, necrotic areas, and bone destruction, characterized histologically as a pyogranulomatous rection. At post mortem examination, a large pyogranuloma was observed in the entire horizontal branch of the mandible as well, showing a dark yellowish content of coarse consistency, caseous appearance, and bone fragmentation. Discussion: Ovine mandibular osteomyelitis is a well-established bone inflammation involving the cortical and medullary regions, characterized clinically by local enlargement, asymmetry, pain sensitivity, edema, hyperthermia, infiltrate caseous or suppurative material, and bone rarefaction. In the current report, 1-month history of progressive enlargement of the mandibular region, prostration, and weight loss in an ewe were referred. Where clinical and epidemiological features, bacteriological, cytological, histological, and mass spectrometry diagnostic approaches were assessed to diagnostic. Most reports involving the etiology of ovine mandibular osteomyelitis have been diagnosed based on classical phenotypic tests. Here, the concomitant identification of P. aeruginosa and L. raffinolactis infection was possible using mass spectrometry (MALDI-TOF), highlighting the importance of molecular methods in the diagnosis of animal diseases. In addition, the differentiation between Lactococcus and Enterococcus species is difficult, which could underestimate the diagnosis of Lactococcus species as a primary pathogen from animal diseases. We report, for the first time, a fatal case of mandibular pyogranulomatous osteomyelitis in a sheep caused by Pseudomonas aeruginosa and Lactococcus raffinolactis coinfection. Keywords: sheep, ovine osteomyelitis, Lactococcus sp., Pseudomonas sp., MALDI-TOF MS.